1989
DOI: 10.1159/000205289
|View full text |Cite
|
Sign up to set email alerts
|

Calla-Positive Acute Leukaemia with t(5q;14q) Translocation and Hypereosinophilia – A Unique Entity?

Abstract: A patient with common acute lymphoblastic leukaemia (ALL), hypereosinophilic syndrome and t(5;14) (q31.1;q32.3) translocation is described. Even with intensive treatment only short periods of complete remission were achieved. Recurrence of the leukaemia was always accompanied by the appearance of eosinophilic granulocytes in the blood and in the bone marrow. Although there is no experimental proof we assume that the hypereosinophilic syndrome is causally related to the chromosome aberration. Translocation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…AML with t [16] or inversion 16 are common genetic abnormalities associated with eosinophilia [6,7]. Most common genetic abnormality detected in case of ALL associated with eosinophilia is t [5,14] which is otherwise uncommon in classical cases of ALL [2,3,[8][9][10]. In general, eosinophilia in association with ALL is rare and that too in T-cell subtype, it is limited to case reports [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AML with t [16] or inversion 16 are common genetic abnormalities associated with eosinophilia [6,7]. Most common genetic abnormality detected in case of ALL associated with eosinophilia is t [5,14] which is otherwise uncommon in classical cases of ALL [2,3,[8][9][10]. In general, eosinophilia in association with ALL is rare and that too in T-cell subtype, it is limited to case reports [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…ALL associated eosinophilia was first reported by Spitzer et al [1]. Some studies have reported association of chromosomal anomaly t [5,14] with eosinophilia associated ALL [2,3]. Whether reactive or clonal, eosinophilia always endangers vital organs at risk of dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Second, leukemic lymphoblasts themselves may produce Eo-CSA. Such a mechanism has been suggested to operate partic ularly in patients with 5q and 14q cytogenetic abnormal ities, which are so common in ALL with eosinophilia [1,6,7]. Third, leukemic lymphoblasts and eosinophils may originate from a common multipotential stem cell [8,9], In the present case, the scrum obtained at the onset of ALL contained a significant amount of Eo-CSA, and T cells obtained at remission produced an increased amount of Eo-CSA with IL-2 stimulation, while leukemic cells pro duced no detectable Eo-CSA, either with or without IL-2 stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilia may be present as a manifestation of acute lymphoblastic leukemia [1][2][3][4]. Several interesting cytogenetic changes have been associated with a subset of this disease [1,4,5] although in some cases, no cytogenetic abnormalities were detected [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several interesting cytogenetic changes have been associated with a subset of this disease [1,4,5] although in some cases, no cytogenetic abnormalities were detected [2,6]. It is possible that some of these cases represent reactive eosinophilia due to an as yet unidentified foreign antigen on leukemic cells.…”
Section: Introductionmentioning
confidence: 99%